Penerapan Model Pembelajaran Problem Based Learning Untuk Meningkatkan Pemahaman Siswa Dalam Pelajaran Bahasa Indonesia - Moh Fadli; Siful Arifin; Lukman Nurhakim (Institut Kariman Wirayudha Sumenep, 2025)
The understanding of second-grade students at Poja II Elementary School in Indonesian language lessons is very lacking and limited. This is evident from passive learning activities and students tend to be unable to answer questions using Indonesian vocabulary. This type of research is Classroom Action Research (CAR) which is carried out in two cycles, both of which have stages of planning, implementation, observation, and reflection. This study aims to determine whether PBL is able to improve students' understanding in Indonesian language lessons. The subjects of this study were second-grade students in the even semester with a total of 33 students consisting of 15 male students and 18 female students at Poja II Elementary School. The data collection techniques used in this study were observation, test, and documentation collection techniques. The results of this study show that: (1) The Problem Based Learning (PBL) learning model can improve the understanding of second-grade students of Poja II State Elementary School in the material of caring for the environment in the Indonesian Language subject in cycle 1 by 65.3% and in cycle 2 by 70% with a good category. (2) The learning outcomes of students using the PBL model in understanding the material of caring for the environment in the Indonesian Language subject for class II achieved an increase from cycle 1 by 63.63% or 21 students achieved learning completeness, and in cycle 2 by 72.72% or 24 students achieved learning completeness with a high category. Thus, it can be concluded that the application of the Problem Based Learning learning model can improve the understanding of Indonesian Language lessons for second-grade students of Poja II State Elementary School.